How loneliness relates to health, wellbeing, quality of life, and healthcare resource utilisation and costs across multiple age groups in the UK - Nia Morrish; Anne Spencer; Antonieta Medina-Lara (PLoS ONE, 2025)
Increasing evidence of its detrimental impact has brought loneliness to the forefront of public health in recent years. Loneliness has been recognised as a cross-cutting theme for Healthy Ageing by the World Health Organisation and there is increasing need to better understand its wide-ranging health, wellbeing, and economic impacts across the wider population. This study utilises data from wave 13(2021–2023) of the Understanding Society UK Household Longitudinal Study to evaluate health and economic outcomes associated to loneliness (UCLA 3-item scale). Outcomes include the General Health Questionnaire, Short Form Health Survey, Short Warwick-Edinburgh Mental Well-being Scale, and costed GP, outpatient, and inpatient visits. Generalised Linear Modelling is applied to adjust for demographic characteristics, and subgroup analysis is conducted to consider costs in different age groups. Complete data provided observations for 23,071 respondents. Average marginal effects found loneliness is associated to higher mental distress, lower positive mental wellbeing, poorer physical and mental functioning, and higher healthcare service use. Overall, there is approximately a £900 cost difference in healthcare use between lonely and non-lonely respondents. Cost difference increases with age, and for more severe loneliness forms a U-shape with the greatest costs in younger and older adults. Additionally, difference in mean is only statistically significant across all models for 16- to 24-year-olds, suggesting importance in targeting young adult healthcare resource use. This is the first study to consider age-based analysis of health-related costs of loneliness in the UK. It also adds to the literature by considering validated wellbeing and health-related outcomes in a large UK based population. Findings motivate tackling young adult loneliness to support their health, wellbeing, quality of life, and potential overuse of healthcare services. This study also supports the pressing need for greater economic evaluation of loneliness and loneliness interventions.